(untitled) (Mugda Medical College Journal, 2024)
Adenoviral ophthalmic infection is a self-limiting, highly contagious, very frequent infectious process. It can present in three acute clinical forms: nonspecific acute follicular conjunctivitis, pharyngo-conjunctival fever and epidemic keratoconjunctivitis. This study aims to assess and compare the efficacy of 0.15% ganciclovir gel with Moxifloxacin eye drop in the treatment of acute adenoviral keratoconjunctivitis.This longitudinal prospective study was conducted among 40 patients of acute adenoviral keratoconjuctivitis attending in the cornea clinic of National Institute of Ophthalmology & Hospital (NIOH), Dhaka, Bangladesh. They were randomly divided into two groups: group-I (study group) with 20 patients who used 0.15% ganciclovir gel and group-ii (control group) with 20 patients who used artificial tear and 0.5% moxifloxacin eye drop. Diagnosis was confirmed by expert cornea specialist by methodical ophthalmic examination. They were followed-up on 1,2,4 and 6 weekly. Mean score of symptoms and signs were calculated in every follow-up and compared between two groups. Unpaired t test and chi square test were done in applicable cases with statistical significance p<0.05. This study showed that in study group mean age of the respondents were 36.4±9.59 years and in control group 37±11.02 years. Most of them were male (82.5%). In study group, mean score of symptoms at the beginning of the study was 1.4. It was 1.14, 0.64, 0.20 and 0.04 after1,2,4,6 weeks respectively after starting treatment and in control group mean score of symptoms at the beginning of the study was 1.48. It was 1.46, 1.125,0.59 and 0.23 after1,2,4,6weeks respectively after starting treatment. A trend towards better response was observed in the treatment group and the difference was statically significant. The mean score of signs after starting treatment in group-iwas 1.8.It was 1.35, 0.775, 0.30 and 0.175 after ,2,4,6weeks respectively and in group-ii, mean score of signs at the beginning of the study was 1.675. It was 1.725,1.35,0.725 and 0.300 after 1,2,4,6 weeks respectively after starting treatment. A trend towards improved sings were observed in the study group and the difference was statistically significant at 1 week (p=0.0283), 2 week (p= 0.0003), 4 week (p=0.0016) except 6 week (p=0.1524). At 6th week of treatment improvement of signs occur but not statistically significant because of persistence of some corneal lesion. The significant symptomatic relief and clinical improvement was found in the study group treated with Ganciclovir ophthalmic gel suggesting an effective method for treatment of acute adenoviral keratoconjunctivitis. Mugda Med Coll J. 2024; 7(1): 9-13